2022
DOI: 10.1186/s12866-022-02702-y
|View full text |Cite
|
Sign up to set email alerts
|

The temporal and spatial endophytic fungal community of Huperzia serrata: diversity and relevance to huperzine A production by the host

Abstract: Background Plants maintain the steady-state balance of the mutually beneficial symbiosis relationship with their endophytic fungi through secondary metabolites. Meanwhile endophytic fungi can serve as biological inducers to promote the biosynthesis and accumulation of valuable secondary metabolites in host plants through a variety of ways. The composition and structure of endophytic fungal community are affected by many factors, including tissues, seasons and so on. In this work, we studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Our study reveals a correlation between HupA content and the diversity distribution patterns of fungi across tissues of H. asiatica, consistent with previous studies on H. serrata [21]. Notably, we observed a distinct pattern in young tissues, such as bulbils and apical shoots, where the fungal diversity was the lowest despite the highest accumulation of HupA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study reveals a correlation between HupA content and the diversity distribution patterns of fungi across tissues of H. asiatica, consistent with previous studies on H. serrata [21]. Notably, we observed a distinct pattern in young tissues, such as bulbils and apical shoots, where the fungal diversity was the lowest despite the highest accumulation of HupA.…”
Section: Discussionsupporting
confidence: 92%
“…Recent research has highlighted the potential of endophytic fungi in HupA production, offering a promising alternative to the challenges associated with natural extraction and chemical synthesis. The mycobiome of Huperzioideae species may play a key role in HupA production, with some fungal species potentially inducing HupA accumulation in the host plants [20][21][22]. Various endophytic fungi have been found to produce HupA independently in culture, without the need for cooperation with the host plant (Supplementary Table S1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, ZC exhibited the highest total flavonoid and phenolic content in its roots, stems, and leaves. The LT leaves displayed higher total flavonoid content, but lower total Numerous studies have demonstrated the influence of endophytic fungi on the secondary metabolite content in plants (Shen et al, 2022;Lu et al, 2023). The results of this study indicated significant differences in the composition and abundance of endophytic fungi among the seven distinct collection sites of Tartary buckwheat materials.…”
Section: The Effect Of Endophytic Fungi On the Content Of Flavonoid M...mentioning
confidence: 56%
“…The seasonal characteristics are associated with the accumulation of active components of Delftia and Sphingomonas paucimobilis in medicinal tissues [17]. The diversity of endophytic fungi in the roots, stems, and leaves of Huperzia serrata varies significantly across different seasons, with lower diversity observed during summer compared to other seasons [18]. Furthermore, research indicates that the season is a key factor in determining the endophytic bacterial community in mulberry trees, followed by host varieties [19].…”
Section: Introductionmentioning
confidence: 99%